Sensory evaluation and consumer acceptability of zinc biofortified rice by farm women in Telangana, India - Waris, Amtul; Neeraja, Chirravuri Naga; Azam, Mohammed Mohibbe; Jangaiah, Battu (Journal of Cereal Research, 2021)
Most of the Indian diets are typically based on cereals and lack micronutrient-rich vegetables, fruits, and flesh foods. The incorporation of zinc biofortified rice in daily diets can help overcome zinc deficiency. The present study aimed to analyze the consumers’ acceptance of zinc biofortified rice as the willingness of consumers to accept it is important for the success of biofortification strategy to combat micronutrient malnutrition. The consumers’ acceptance of zinc biofortified rice in terms of its hand feel mouth feel texture, taste, and overall acceptability was determined using the Five-point Hedonic scale. Hand-pounded samples of zinc biofortified rice and control were provided to sixty farm women to evaluate by the Home Use Test protocol. The index of acceptability (IA) was worked out for the acceptance of zinc biofortified rice and was found to be greater than 70% for all the parameters. The consumers’ socio-economic characteristics did not show a significant relationship with the acceptability of zinc biofortified rice except for hand feel texture. Based on the hedonic categorization suggested by Belmes (2019), the overall acceptability of both the zinc biofortified rice and control are in the acceptable category of hedonic rating. Therefore it can be concluded that the zinc biofortified rice variety DRR Dhan 45 is equally acceptable to the consumers as the control rice. The consumers’ socio-economic characteristics did not show a significant relationship with the acceptability of zinc biofortified rice. The zinc biofortified rice can be promoted for use in daily diets to help meet the zinc needs of the family and included in the nutrition intervention programs of the country for overcoming micronutrient malnutrition.